Foliar manganese, zinc and boron application effects on mineral nutrition of an experimental olive grove (cv. "Chondrolia Chalkidikis"). (21st July 2017) - Chatzistathis, T.; Delviniotis, A.; Panagakos, A.; Giannakoula, A.; Tranaka, V.; Molassiotis, A.
ABSTRACT: A 6-month field experiment (from October to March) was conducted in a 20-year-old experimental grove of the Aristotle University of Thessaloniki in order to enhance its micronutrient levels and assess the effect of micronutrient foliar application manganese, zinc and boron (Mn, Zn and B) on mineral nutrition, chlorophyll concentration and chlorophyll fluorescence parameters (Fv /Fm, Fv /F0 and Performance index, PI) of the olive trees (cv. "Chondrolia Chalkidikis"). The experiment consisted of four treatments (Control-C: trees sprayed with deionized water, T50: trees sprayed with 50 mg/L Mn, Zn and B, T100: trees sprayed with 100 mg/L Mn, Zn and B, T200: trees sprayed with 200 mg/L Mn, Zn and B); the three micronutrients were applied in the forms of manganese sulfate (MnSO4 ), zinc sulfate (ZnSO4 ) and boric acid (H3 BO3 ), respectively. The results showed that the most effective treatment for the enhancement of foliar Mn and B levels was T200, while for the increase of Zn levels was T100. In addition, significant differences among the treatments were recorded for most leaf nutrient concentrations (with the exception of potassium (K), which was not influenced by foliar treatment, the other macronutrients, such as calcium (Ca), magnesium (Mg), phosphorus (P) and nitrogen (N), as well as iron (Fe), obtained their maximum concentrations, at the end of the experiment, in C or T50 treatment). Chlorophyll concentrations were not influenced by foliar treatment. Concerning chlorophyll fluorescence parameters (Fv /Fm, Fv /F0 and P index), significantly lower values were found in the control (C) trees, compared to the other three treatments, so it seems that a chlorophyll fluorescence technique may be used to detect micronutrient deficiencies in olive groves. However, from all the leaf nutrient concentrations determined, it was found that with the exceptions of: 1) Mn concentrations in the C, T50 and T100 treatments, which were marginal, or slightly deficient; 2) B and Zn concentrations in the C and T50 treatments, which were slightly deficient and marginal, respectively; 3) some K concentrations during the early spring period, which were slightly deficient, all the other concentrations were within the normal levels of sufficiency or within the optimum range, so no serious nutrient deficiency was detected.